A path detecting method to analyze the interactive compatibility of service processes based on WS‐BPEL. (7th June 2018) - Hu, Qiang; Liu, Minghua; Zhao, Zhen; Du, Junwei
Summary: Petri nets are frequently used formal tools to analyze the compatibility of interactive service processes described by Web Services Business Process Execution Language (WS‐BPEL). However, the traditional methods based on Petri nets were with a high computable complexity for state space explosion. To resolve such problem, a logic Petri net–based path detecting method for compatibility analysis of interactive service processes is proposed. From the provided mapping rules, the service process described by WS‐BPEL is modeled as a service net based on logic Petri nets. The evaluation of interactive compatibility of two service processes is converted to analyze whether their service nets can be composed as a non‐blocked synthetic service net. The non‐blocked property is checked by detecting the reachability of the potential connected paths in a service net. To reduce the complexity of computing the connected paths in a service net, we propose a merge‐reduced method to generate the path expression of its skeleton service net. The potential connected paths of a service net can be obtained by unfolding the path expression. Compared with the traditional method based Petri nets, the proposed method is with high efficiency and it can greatly alleviate the problem of state space explosion in analyzing interactive compatibility of service processes.